Characteristics of soil microbial biomass and community composition in Pinus yunnanensis var. Tenuifolia secondary forests. (17th November 2018) - Yu, Sufang; She, Guanghui; Ye, Shaoming; Zhou, Xiaoguo; Yao, Xianyu; Li, Yuanfa
ABSTRACT: Pinus yunnanensis var. Tenuifolia is an important species of timber and grease in southern China, but the characteristics of the soil microbial community in P. yunnanensis var. natural secondary forests are still poorly understood. Using a fumigation-extraction method and phospholipid fatty acid (PLFA) analysis, we study microbial biomass and community composition in the topsoil (0–10 cm) of three types of secondary forests (PYI, PYII, PYIII) dominated by P. yunnanensis var. to varing degrees. Microbial biomass carbon and nitrogen, total PLFA, and PLFA contents of bacterial, fungal, and arbuscular mycorrhizal fungi were significantly lower in PYI than PYII or PYIII, and there were significant differences in the monounsaturated/saturated fatty acid ratio among the tested forests. Principal component analysis indicated that the soil microbial community structure of the tested forests differed significantly. The changes in soil microbial biomass and community composition were positively correlated with soil water content, pH, organic matter (SOM), total nitrogen (TN), and total phosphorus. Season did not significantly affect the soil microbial community structure, but significantly affected soil microbial biomass, SOM, and TN, which were higher in the dry season than in the wet season.